Shareholders' duties - Birkmose, Hanne S. (European company law series ;, 2017)
This book provides a systematic overview of shareholders' duties found in European company law and capital market law. It is often assumed that shareholders have rights, not duties. In recent years, however, this assumption has come under intense scrutiny in all aspects of company law, and scholarship. In Europe especially, major changes are under way across a diverse spectrum, all the way from revised contractual arrangements to mandatory statutory provisions. Such a shift has important implications for the fundamentals of European company law, and there is a need to examine shareholders' duties and consider where this trend is taking shareholders and their stance in law. This focused collection of essays addresses this complex subjects from highly informative and useful variety of perspectives --